PENGARUH PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SENI RUPA SISWA DI SMP NEGERI 39 PADANG - Hari Perwansyah, Drs. Eswendi, M.Pd., Drs. Yusron Wikarya, M.Pd. (Universitas Negeri Padang, 2018)
The purpose of this research is to know the influence of the use of learning discovery learning model to the learning result of Fine Arts students SMPN 39 Padang. This type of research is an experimental study that applies quasi experimental pretest posttest control group design. The population in this study were all students of SMPN 39 Padang who studied art. The sample in this esearch use purposive random sampling technique. The data source is a written test given to the students. The data obtained were then analyzed statistically. he test consists of multiple questions about applied art theory. T-test was used to prove the hypothesis of this study. By using the application of learning discovery learning model positively significant in the level of 5% of the learning outcomes that are taught using conventional methods.Keywords: Learning model, discovery learning, art learning, learning result